No Fault Found events in maintenance engineering Part 2: Root causes, technical developments and future research - Khan, Samir; Phillips, Paul; Hockley, Chris; Jennions, Ian K. (Elsevier, 2013)
This is the second half of a two paper series covering aspects of the no fault found (NFF) phenomenon, which is highly challenging and is becoming even more important due to increasing complexity and criticality of technical systems. Part 1 introduced the fundamental concept of unknown failures from an organizational, behavioral and cultural stand point. It also reported an industrial outlook to the problem, recent procedural standards, whilst discussing the financial implications and safety concerns. In this issue, the authors examine the technical aspects, reviewing the common causes of NFF failures in electronic, software and mechanical systems. This is followed by a survey on technological techniques actively being used to reduce the consequence of such instances. After discussing improvements in testability, the article identifies gaps in literature and points out the core areas that should be focused in the future. Special attention is paid to the recent trends on knowledge sharing and troubleshooting tools; with potential research on technical diagnosis being enumerated.
Keywords: No fault found; Test equipment; Troubleshooting failures; Fault diagnostics; Maintainability; Testability